2011
DOI: 10.1258/jtt.2010.100602
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of home telerehabilitation for post-knee arthroplasty

Abstract: We compared the effectiveness of home telerehabilitation with conventional rehabilitation following knee replacement surgery (total knee arthroplasty, TKA). Forty-eight patients (mean age 66 years) who received TKA were recruited prior to discharge from hospital after surgery and were randomly assigned to telerehabilitation or usual care. Telerehabilitation sessions (16 per participant over two months) were conducted by trained physiotherapists using videoconferencing to the patient's home via an Internet conn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
270
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 192 publications
(283 citation statements)
references
References 20 publications
8
270
0
5
Order By: Relevance
“…Data were available at one or more time points for five studies with 437 patients. 520,592,594,595,602 As shown in Table 96 and Figure 52, there was no suggestion of a difference in functional outcome between home and outpatient provision at 3-4, 6 or 12 months. For example, at 3-4 months, the average SMD was -0.03 (95% CI -0.25 to 0.19; p = 0.80).…”
Section: 601mentioning
confidence: 88%
See 4 more Smart Citations
“…Data were available at one or more time points for five studies with 437 patients. 520,592,594,595,602 As shown in Table 96 and Figure 52, there was no suggestion of a difference in functional outcome between home and outpatient provision at 3-4, 6 or 12 months. For example, at 3-4 months, the average SMD was -0.03 (95% CI -0.25 to 0.19; p = 0.80).…”
Section: 601mentioning
confidence: 88%
“…No heterogeneity was apparent and consideration of higher-quality studies only marginally affected the outcome at 3-4 months in two studies (average SMD -0.15, 95%CI -0.43 to 0.13; p = 0.29), in favour of home-based rehabilitation. 520,595,602 As shown in Table 96 and Figure 53, there was no difference in pain outcome between patients randomised to home-based or outpatient physiotherapy exercise (average SMD -0.00, 95% CI -0.25 to 0.25; p = 0.98). One study 595 followed up 85 and 92 patients at 6 and 12 months and showed no benefit for reduced pain at either follow-up.…”
Section: 601mentioning
confidence: 91%
See 3 more Smart Citations